2017
DOI: 10.1093/ntr/ntx091
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Cigarettes Leads to Significant Beta2-Nicotinic Acetylcholine Receptor Occupancy: Evidence From a PET Imaging Study

Abstract: This is the first study to directly determine the neurologic effects of electronic cigarettes on human brain beta-2 nicotinic acetylcholine receptors using PET neuroimaging with (-)-[18F]Flubatine, a novel radiotracer. Our findings suggest that the e-cigarettes studied here have abuse liability and may provide an adequate alternative nicotine delivery system for cigarette smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…First, imaging may identify patients with hypocholinergic function to select for cholinergic pharmacotherapy augmentation studies. Second, cholinergic ligand studies may be used for target engagement studies of novel compounds using target displacement techniques (Baldassarri et al, 2018). PET studies combining nicotinic and muscarinic ligands may be vey useful for improved selection of cholinergic compounds to mitigate specific clinical symptoms in PD.…”
Section: Discussionmentioning
confidence: 99%
“…First, imaging may identify patients with hypocholinergic function to select for cholinergic pharmacotherapy augmentation studies. Second, cholinergic ligand studies may be used for target engagement studies of novel compounds using target displacement techniques (Baldassarri et al, 2018). PET studies combining nicotinic and muscarinic ligands may be vey useful for improved selection of cholinergic compounds to mitigate specific clinical symptoms in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is emerging suggesting compensatory behaviours occur in response to this variation, in a manner similar to that identified in cigarettes several decades ago [36]. Electronic cigarettes are as capable of saturating brain nicotinic receptors as conventional cigarettes [37]. This effect may not concur with the nicotine content listed on refill bottles, which may reflect inaccuracy of labelling and manufacturing.…”
Section: Electronic Cigarettes and Nicotine Addictionmentioning
confidence: 98%
“…In this context, 2-[ 18 F]FA has been applied to reveal changes in α4β2 nACh receptor, for example by cigarette smoking showing that that smoking of one cigarette produced almost 90 % receptor occupancy 65 . Another study indicated that the use of electronic cigarettes leads to dose-dependent significant β2-nACh receptor occupancy together with reduction of craving similar with the use of a tobacco cigarette 66 .…”
Section: Types Of Challenges That Modulate Neurotransmission and mentioning
confidence: 99%